CD155/PVR plays a key role in cell motility during tumor cell invasion and migration. - Sloan, Kevin E.; Eustace, Brenda K.; Stewart, Jean K.; Zehetmeier, Carol.; Torella, Claudia.; Simeone, Marina.; Roy, Jennifer E.; Unger, Christine.; Louis, David N.; Ilag, Leodevico L.; Jay, Daniel G. (2016)
Background: Invasion is an important early step of cancer metastasis that is not well understood. Developing therapeutics to limit metastasis requires the identification and validation of candidate proteins necessary for invasion and migration.; Springer Open.